The Country and the City in the Irish Novel, 1922-51 - O'NEILL, STEPHEN BERNARD (Trinity College Dublin. School of English. Discipline of English, 2018)
This thesis investigates the representation of the country and the city in the Irish novel north and south after partition. The political success of both Irish nationalism and Ulster unionism were partly shaped by a popular understanding of the north as urban and the south as rural in culture and politics. After the ensuing establishment of the northern and southern states, writers used fiction both in response to the dominant discourses of state formation, and as a means of recording what Raymond Williams calls ?immediate living experience? as a form of redress to this political rhetoric. Resituating the novel in these years after partition, this thesis examines the changing and contradictory uses of the rural and the urban over the course of the 1922-51 period. Drawing upon a range of expressions of the country and the city in rhetoric, exhibitions, journalism, and other cultural outputs, the thesis argues that the country and the city were the axial lines upon which the novel and national identity were charted.
APPROVED
Keywords: urban; partition; nationalism; Irish Novel; unionism; Raymond Williams; rural